Conservation Based on Local Wisdom (Case Study: Bakalili Crowded in Labuhan Burung Sumbawa Village) - Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The busy bakalili tradition is one of the activities that helps maintain the conservation of marine natural resources because it involves the community in its management and is the main attraction for tourists who want to know and experience the authentic culture of Labuhan Burung village. This research aims to analyze the role of local wisdom in maintaining the sustainability of marine resources through conservation traditions. This research uses a descriptive qualitative approach by analyzing data obtained through literature, field observations, interviews, photos and documentation. The results of the research explain that the busy bakalili tradition is not just a tradition of catching shellfish, snails, crabs and others, but can reflect the culture and local wisdom of the people of Labuhan Burung Village in managing marine resources. The sustainability of this busy bakalili tradition is strengthened by the community's collective awareness of the importance of conservation, as well as depicting a good balance between ecology and culture.